OPERATION SINDOOR AND THE FINANCIAL SECTOR: ANALYZING LIC’S CONTRIBUTIONS TO ECONOMIC STABILITY AND GROWTH IN THE KASHMIR VALLEY - Dr. Vandna Sharma,; Dr Monika Khanna,; Dr Anchal Yadav,; Dr Nidhi Bansal,; Dr Priya Saini,; Dr Pritam Singh, (IJRDO - Journal of Social Science and Humanities Research, 2025)
Operation Sindoor, launched in May 2025, marked a decisive military and strategic effort by the Indian government to restore stability in the conflict-affected Kashmir Valley. Beyond the immediate security outcomes, the operation created conditions for economic re-engagement and institutional rebuilding. This study examines the role of the Life Insurance Corporation of India (LIC) as a key financial actor in the region’s post-conflict recovery. LIC’s expanded insurance coverage, rapid claim settlements, infrastructure investments, and community-level outreach are analyzed as instruments of both economic stabilization and public trust-building. Drawing on LIC annual reports (2014–2024), government data, and regional economic surveys, the research adopts a comparative approach to assess LIC’s evolving footprint before and after the operation. Findings indicate that LIC played a significant role in enhancing financial inclusion, employment generation, and public confidence in formal institutions, thereby contributing to long-term peacebuilding efforts in Kashmir.